Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Kedai Kopirates Di Kabupaten Sikka - Witak, Barbara Karin; Rangga, Yoseph Darius Purnama; Gula, Valeria Eldyn; Pareira, Stefanus Genosius Selong (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the influence of product quality and price on customer satisfaction at Kopirates Coffee Shop in Sikka Regency. The research employed a quantitative approach using a survey method involving 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that both product quality and price have a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination (R²) of 0.700 shows that 70% of the variation in customer satisfaction can be explained by product quality and price, while the remaining 30% is influenced by other factors outside the research model. These findings emphasize the importance of maintaining high product quality and implementing appropriate pricing strategies to enhance customer satisfaction.